The Value of Kiai's Wisdom in Reducing Cases of Violence in Islamic Boarding Schools: Perspective of Article 50 of Law No. 23 of 2002 concerning Child Protection - Supriyanti, Iin; Fatmawati, Indah (Sekolah Tinggi Agama Islam (STAI) Darul Ulum Banyuanyar Pamekasan, 2025)
aw Number 35 of 2014 concerning Child Protection emphasizes that the state, society, and family share responsibility for ensuring children’s protection, including within Islamic boarding schools (pesantren). However, instances of violence against students—many of whom are still children—highlight the need for approaches grounded in moral and spiritual values. This study aims to explore how kiai wisdom values contribute to reducing violence against children in pesantren, analyzed through the perspective of Law Number 35 of 2014. Employing a qualitative field research method, primary data were collected from kiai at Pondok Pesantren Tahfidzul Qur’an Rodliyatan Mardiyah, Ngoro District, Jombang, while secondary data involved santri, ustadz/ustadzah, murobbi, and walisantri. The data were analyzed deductively using the theory of kiai wisdom values and child protection law. The findings show that moral education based on kiai wisdom—such as prohibiting harsh speech, promoting gentleness, and emphasizing ethical behavior—effectively reduces both verbal and physical violence among students. These practices align with the Child Protection Law, ensuring children’s right to safety within educational environments. The study contributes to understanding how traditional Islamic educational values can synergize with national legal frameworks to foster child protection and character development in pesantren.